Integrating Outdoor Wind Simulation in Urban Design : A Comparative Study of Simulation Tools and their Benefits for the Design of the LTU Campus in Luleå - Broekhuizen, Ico (2016)
Wind is presently not considered enough in urban planning projects, which can lead to uncomfortable or even dangerous outdoor conditions for pedestrians. This is at least partially caused by a lack of knowledge among urban planners about wind simulation. This paper examines how urban planners can better integrate wind simulation in the design process. Several wind simulation tools are compared to determine how accurate and usable they are for urban planners using a case study of the LTU campus. General-purpose CFD software (Autodesk CFD) is found to be both more accurate and user-friendly than a simple CFD program (Autodesk Flow Design) or a building energy simulation program (DesignBuilder). Finally, a demonstration is given of how a wind simulation carried out in Autodesk CFD can significantly improve the existing master plan for the LTU campus by making minor modifications to the proposed layout. Validerat; 20160129 (global_studentproject_submitter)